HUMANISTIC ASPECTS OF ECOLOGICAL VALUES IN BUDDHISM AND TAOISM AND THEIR SOCIAL SIGNIFICANCE - Лазоревич, Ірина (The Ukrainian Center for Cultural Studies, 2021)
The tendency to seek the harmonization of the relationship between nature and man is as rele vant as ever. In the social value discourse, increase in the role of religion and religions in public space encourages religions themselves to become useful to society with their environmental narratives, and society – to be more attentive to their potential. After all, now the answers to the question of how to save humanity without global losses and how to move from a destructive type of development to a regulated one are as relevant as ever. How to mobilize moral and intellectual potential? It is obvious that global problems affect absolutely all segments of the population: Christians and Buddhists, agnostics and atheists. Undoubtedly, these issues concern churches and their spiritual leaders. In the article, the author reveals humanistic aspects of ecological ideas of the East (on the example of Buddhism and Taoism), explains the resource of Buddhist and Taoist environmental wisdom in its heuristic possibilities for today. Relevant guidelines are impor tant for analysis and reflection, at least because they have mentally shaped the ecological culture of its adherents. And as is known, the ecological construct of a number of Eastern countries is recognized in the West as worthy of approval and imitation for the formation of a model of sus tainable development and potential establishment of environmentally friendly society. The author focuses not so much on the dogmatic features of the substantiation of Buddhist and Taoist ideas (in tendencies and directions), as on the identification of their common humanistic logic, which can be understood and accepted by Western people (they do not have to become the followers of relevant Eastern doctrines). The researcher also considers the value potential of the worldview cultures in the aspect of sacralization of the rhythms of nature, reverence for its beauty as an image of wise cosmic “industry”. The article implements the disciplinary interaction of religious studies, applied ethics, aesthetic hermeneutics.
Keywords: Buddhism, Taoism, culture, karma, ahimsa, ecology, global problems.